Students’ competitiveness: motivation or fear? - Wu, Lin; Purwaningrum, Evi Kurniasari; Ho, Yi Ming; Prihadi, Kususanto Ditto; Cheng, Chen; Qian, Kuang (Intelektual Pustaka Media Utama, 2025)
This study aimed to explore the factors that contribute to the high level of competitiveness among students in the People’s Republic of China (PRC). The expectancy value theory has suggested that the fear of failure (FOF) and a highly perceived value for achievement (expectancy value belief, EVB) are the key drivers of competitiveness. To examine this theory, the study analyzed data from 969 college students in the PRC using Bootstrap Analysis with 5,000 samples in a 95% confidence interval. The study found that while the value placed on academic achievement did motivate students to fear failure and become more competitive, perceived social support played a significant role in moderating this relationship. Specifically, the students’ perception of social support moderated the mediation of (FOF) on the link between EVB and competitiveness. These findings suggest that social support is a crucial factor in shaping the dynamics of competitiveness among PRC students. The study may have implications for educators and policymakers seeking to promote healthy competition and academic achievement in highly competitive education systems.